pengembangan PENGEMBANGAN MODUL BERBASIS QR CODE UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI PERSAMAAN KUADRAT DI KELAS IX MTS NURUL HUDA BERCAK ASRI CERMEE BONDOWOSO: pengembangan modul berbasis qr code - fredi yatmo dwi harjo, fredi (Universitas Mercu Buana Yogyakarta, 2024)
Interest in learning is also the key to success in learning. Interest in learning is doing a learning activity to increase knowledge and skills as well as experience and driving force from within each individual. The development of a QR Code-based module was carried out to increase students' interest in learning quadratic equations. The research was conducted at MTs Nurul Huda Bercak Asri Cermee Bondowoso. The subjects used were class X students. The research method used in this study is Research and Development with a four-D model, namely, define, design, develop and disseminate. The expert validation test was carried out by 3 experts with a percentage of test results, namely linguists 93.3%, media 80% and materials 93.3%. For the practicality test, the researcher used 2 stages, namely teacher activity analysis and student activity analysis. With the percentage of teacher activity analysis results of 80%, student activity 87.3%. While for the effectiveness test of learning devices, it was carried out through 2 assessments, namely student response questionnaires and KKM completion. Based on the research that has been carried out, the results obtained were, student response questionnaires 83.3% and KKM completion 86%. After the learning device test was carried out, a validity test, reliability test and T-Test test were carried out. The results of the validity test that had been carried out were valid with the acquisition of r-calculated data above the provisions of all r-tables. The reliability test also showed reliable decisions. While for the T-Test test there was also an increase in student learning outcomes.